Introduction to Special Issue - Hiebert, Bryan (Canadian Journal of Counselling and Psychotherapy, 1992)
In 1989 the Canadian Guidance and Counselling Foundation (CGCF) launched a 15-million-dollar national initiative directed at effecting a substantial improvement in career counselling in order to enable more youth to enter the labour market without serious difficulty and then to participate in it more effectively. The initiative was entitled 'The Creation And Mobilization of Counselling Resources for Youth" or CAMCRY. CAMCRY represents a partnership between a foundation, universities and colleges, provincial governments, private business, and several professional associations and Employment and Immigration Canada (EIC Thus, CAMCRYis likely the largest single research and program development endeavour in the history of counselling in Canada in terms of amount of funding, scope of involvement, and number of projects. This special issue of the Canadian Journal ofCounselling contains a cross-section of reports on various projects. This introductory paper documents the background events giving rise to CAMCRY, highlighting the novel and collaborative aspects ofthe initiative, in the hope that others might benefit from our experience in research and program development. Currently, there are 41 CAMCRY projects nearing completion or already completed. The papers reported in this special issue of the Canadian Journal of Counselling have all been developed under the CAMCRY initiative. The field test results and/or the conceptual development of the programs are the focus of the papers. In fact, the response to the call for papers, and the number of papers receiving positive reviewer recommendations, was so great that it was necessary to spread the papers dealing with CAMCRY projects across two issues of CJc. Thus, this issue will highlight several CAMCRY projects and the next issue of CJCwill contain the remaining papers. Collectively, these papers provide a glimpse of new developments in career counselling for youth, a focus which many believe will become increasingly important in the future.